Stroke and gender identity in teacher success: from learners’ viewpoints - Noorbakhsh, Zahra; Pishghadam, Reza; Saboori, Fahime (National Science Foundation: Colombo, 2018)
The purpose of the present study was to explore the roles of teacher gender identity and stroke in teacher success. All variables were viewed from the learners’ viewpoints. Three scales were used to measure stroke, teacher gender identity and teacher success. The participants consisted of 287 English learners in private language institutes. To analyse the data, first Pearson product-moment correlation was used, the results of which revealed significant relationships among all these variables. Next, Path Analysis was employed to examine the predictive power of teacher gender identity and stroke in teacher success. The findings indicated that femininity and masculinity predicted stroke and that stroke and androgyny were positive predictors of teacher success.
Keywords: Teacher success; Gender identity; Stroke